Sarcomatous intrahepatic cholangiocarcinoma: Case report and literature review. Issue 39 (September 2018) - Zhang, Ning; Li, Yatong; Zhao, Mengyun; Chang, Xiaoyan; Tian, Feng; Qu, Qiang; He, Xiaodong
Abstract: Rationale: Sarcomatous intrahepatic cholangiocarcinoma is a rare histological variant of cholangiocarcinoma (ICC). Previous medical literature has not mentioned the prevalence of this kind of disease, but a poorer prognosis than that of ordinary ICC was indicated. The diagnosis of the sarcomatous ICC is established on histopathological and immunohistochemical examinations. In this article, we present a new case of a patient with sarcomatous ICC who had no radiographic sign of intrahepatic tumor preoperatively. Patient concerns: A 63-year-old man was noted with cholecystolithiasis and right upper abdominal pain. Liver function was within normal limits, although the gamma-glutamyl transpeptidase level was elevated. Serum carbohydrate antigen 19-9 level was elevated. Radiography showed atrophy of the left lobe of the liver, high-intensity signals on T1 weighted images, and low/high-intensity signals on T2 weighted images in hepatic ducts. Diagnoses: The preoperative diagnoses were hepatolithiasis, choledocholithiasis, and cholecystolithiasis. Interventions: Exploratory laparotomy, adhesion release, cholecystectomy, choledocholithotomy, and T tube drainage were performed. During the surgery, an ill-defined tumor was detected on the atrophic left lateral lobe of the liver. Hepatic left lateral lobectomy was performed to remove the mass. Outcomes: The final diagnosis of sarcomatous ICC was made by histopathology after surgery. No evidence of local recurrence or distant metastasis was noted on imaging during follow-up. Lessons: Although rare, sarcomatous ICC does exist in patients presented with cholecystolithiasis and liver atrophy. Surgeons should be aware of the existence of sarcomatous ICC due to the poor prognosis. We recommend that multidisciplinary approaches may be key to improve prognosis, including adjuvant chemotherapy or radiotherapy.